Multiple N—H...NC, C—H...NC and nitrile...π interactions in 4, 4′‐bipyridine‐1, 1′‐diium bis(1, 1, 3, 3‐tetracyano‐2‐ethoxypropenide): structure determination and DFT calculations of anion...π cation interaction energies. Issue 8 (7th July 2015) - Setifi, Fatima; Geiger, David K.; Abdul Razak, Ibrahim; Setifi, Zouaoui
<x xml:space="preserve">Abstract</x> Polynitrile anions are important in both coordination chemistry and molecular materials chemistry, and are interesting for their extensive electronic delocalization. The title compound crystallizes with two symmetry‐independent half 4, 4′‐bipyridine‐1, 1′‐diium (bpyH22+) cations and two symmetry‐independent 1, 1, 3, 3‐tetracyano‐2‐ethoxypropenide (tcnoet−) anions in the asymmetric unit. One of the bpyH22+ ions is located on a crystallographic twofold rotation axis (canted pyridine rings) and the other is located on a crystallographic inversion center (coplanar pyridine rings). The ethyl group of one of the tcnoet− anions is disordered over two sites with equal populations. The extended structure exhibits two separate N—H...NC hydrogen‐bonding motifs, which result in a sheet structure parallel to (010), and weak C—H...NC hydrogen bonds form joined rings. Two types of multicenter CN...π interactions are observed between the bpyH22+ rings and tcnoet− anions. An additonal CN...π interaction between adjacent tcnoet− anions is observed. Using density functional theory, the calculated attractive energy between cation and anion pairs in the tcnoet−...π(bipyridinediium) interactions were found to be 557 and 612 kJ mol−1 for coplanar and canted bpyH22+ cations, respectively.